Pancreatic cancer incidence and survival and the role of specialist centres in resection rates in England, 2000 to 2014: a population-based study - Exarchakou, Aimilia; Papacleovoulou, Georgia; Rous, Brian; Magadi, Winnie; Rachet, Bernard; Neoptolemos, John P.; Coleman, Michel P. (Pancreatology, 2020)
Background - The aim was to compare population-based survival for exocrine pancreatic cancer in England in the 23 regions covered by specialist centres. The centres were initiated in 2001, covering populations of 2-4 million. - Methods - We examined incidence for adults diagnosed with a pancreatic exocrine cancer during 1995-2014 and age-standardised net survival up to five years after diagnosis for patients diagnosed during 2000-2013. We examined variation in regional resection rates and survival for patients diagnosed during 2010-2013. The data were extracted from the National Cancer Registration and Analysis Service. - Results - Age-standardised annual incidence rates of exocrine pancreatic cancer increased from 17.1 per 100,000 during 1995-1999 to 18.7 during 2010-2014. Age-standardised one-year and five-year net survival increased from 17.9% and 3.6%, respectively, for 2000-2009, to 21.6% and 4.2% during 2010-2013. There were 2086 (8.9%) resections among 23,415 patients diagnosed with an exocrine tumour in 2010-2013. The proportion ranged from 5.1% to 19.6% between centres. Among resected patients, survival was 73.0% at one year and 20.2% at five years. Of the total 2118 resected patients, 18 (0.9%) were at stage 1; 34 (1.6%) at stage 2; 791 (37.3%) at stage 3 and 140 (6.6%) at stage 4, although 53.6% of stage information was missing. Five-year survival was 2.1% for those who were not resected. The number of resections performed in each centre was not correlated with one-year survival. - Conclusions - Despite improvements in the management of pancreatic cancer in England with the introduction of specialist centres, resection rates remain relatively low, and survival remains lower than in comparably wealthy countries.